Trophic niche similarities of sympatric Turdus thrushes determined by fecal contents, stable isotopes, and bipartite network approaches. Issue 17 (17th August 2020) - Bosenbecker, Camila; Bugoni, Leandro
Abstract: An ecological niche has been defined as an n ‐dimensional hypervolume formed by conditions and resources that species need to survive, grow, and reproduce. In practice, such niche dimensions are measurable and describe how species share resources, which has been thought to be a crucial mechanism for coexistence and a major driver of broad biodiversity patterns. Here, we investigate resource partitioning and trophic interactions of three sympatric, phylogenetically related and morphologically similar species of thrushes ( Turdus spp.). Based on one year of data collected in southern Brazil, we investigated niche partitioning using three approaches: diet and trophic niche assessed by fecal analysis, diet and niche estimated by stable isotopes in blood and mixing models, and bipartite network analysis derived from direct diet and mixing model outputs. Approaches revealed that the three sympatric thrushes are generalists that feed on similar diets, demonstrating high niche overlap. Fruits from C3 plants were one of the most important food items in their networks, with wide links connecting the three thrush species. Turdus amaurochalinus and T. albicollis had the greatest trophic and isotopic niche overlap, with 90% and 20% overlap, respectively. There was partitioning of key resources between these two species, with a shared preference for fig tree fruits— Ficus cestrifolia ( T. amaurochalinus PSIRI% = 11.3 and T. albicollis  = 11.5), which was not present in the diet of T. rufiventris . Results added a new approach to the network analysis based on values from the stable isotope mixing models, allowing comparisons between traditional dietary analysis and diet inferred by isotopic mixing models, which reflects food items effectively assimilated in consumer tissues. Both are visualized in bipartite networks and show food‐consumers link strengths. This approach could be useful to other studies using stable isotopes coupled to network analysis, particularly useful in sympatric species with similar niches. Abstract : Niche dimensions are measurable and describe how species share resources, which has been thought to be a crucial mechanism for coexistence and a major driver of broad biodiversity patterns. Morphologically, similar species of thrushes ( Turdus spp.) are generalist species, but distinct, despite overlapping feeding habits allow coexistente.